A BRIEF STUDY ON THE APPLICATIONS OF EXPERIMENTAL MODAL ANALYSIS - Kanhaiya Prasad; Dr. Awari Mahesh Babu (Innovative Research Thoughts, 2021)
The process of making adjustments or alterations to the mass, stiffness, and damping of the system is referred to as structural dynamic modification (often abbreviated as SDM). Whenever there is a change in the state of any of the entities, the dynamic behaviour of the system will adapt accordingly. With the use of a modal model, one may run a comprehensive simulation in order to make an accurate forecast of how the system would react to a change in any of its physical quantities. This "What if" analysis gives the analyst important information that can be used to change the dynamic of the system. The process of SDM may be repeated on the system while it is in a virtual environment, which saves the time and money that would otherwise be spent on the Design-Build-Test process.